Representation of Women in W. B. Yeats’ Poetry: A Biographical Study: Exploring the Impact of Women on W. B. Yeats' Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The artistic career of W.B.Yeats, one of the main exponents of modern British Poetry came under the powerful spell of a few women of his time, who not only made important contribution to Yeats’ poetic development but moulded his personality as well. The present article proposes to be a biographical study of some of these influences upon Yeats, based on a few well-known biographies of the poet, and a few related critical studies. Instead of broadening its perspective into the socio-political frame of the poet’s time the paper chooses to confine itself to the ebb and flow of fathomless sorrow and the pinnacle of joy experienced by a hyper-sensitive mind.